Sequential utilization of hosts from different fly families by genetically distinct, sympatric populations within the Entomophthora muscae species complex. - Andrii P Gryganskyi (Public Library of Science (PLoS), 2013)
The fungus Entomophthora muscae (Entomophthoromycota, Entomophthorales, Entomophthoraceae) is a widespread insect pathogen responsible for fatal epizootic events in many dipteran fly hosts. During epizootics in 2011 and 2012 in Durham, North Carolina, we observed a transition of fungal infections from one host, the plant-feeding fly Delia radicum, to a second host, the predatory fly Coenosia tigrina. Infections first appeared on Delia in the middle of March, but by the end of May, Coenosia comprised 100% of infected hosts. Multilocus sequence typing revealed that E. muscae in Durham comprises two distinct subpopulations (clades) with several haplotypes in each. Fungi from either clade are able to infect both fly species, but vary in their infection phenologies and host-specificities. Individuals of the more phylogenetically diverse clade I predominated during the beginning of the spring epizootic, infecting mostly phytophagous Delia flies. Clade II dominated in late April and May and affected mostly predatory Coenosia flies. Analysis of population structure revealed two subpopulations within E. muscae with limited gene exchange. This study provides the first evidence of recombination and population structure within the E. muscae species complex, and illustrates the complexity of insect-fungus relationships that should be considered for development of biological control methods.